PEMBENTUKAN GYARUGO DALAM MANGA MY DRESS UP DARLING: English - Ramdan Suhendar, Ikbal (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2024)
The term "Gyaru" refers to a group of Japanese women who are distinguished by their unique fashion style, as well as their language, which is known as "Gyarugo." Gyarugo is one of the pioneers of the term wakamono kotoba, which is frequently employed by young Japanese people. This study aims to explain the use of gyarugo in the manga 'My Dress Up Darling', which focuses on the main heroine Marin Kitagawa, which is reviewed based on the formation of wakamono kotoba theory Yonekawa (1996). The data source for this study is volume 1 (chapters 1 to 7) of the manga My Dress Up Darling by Shinichi Fukuda, published in the Young Gangan manga magazine on 19 January 2018. The research method employed in this study is qualitative, while the technique utilised is that of listening and note-taking. The results obtained are the use of 48 gyarugo, as expressed by Marin Kitagawa, which consists of 4 Shakuyou, 39 Shouryaku, 1 Touchi, 5 and Doushi no hasei.